Tinjauan Kinerja Belanja Daerah Pemerintah Kota Jayapura - Daniel Duwiri (PT PUSTAKA CENDEKIA GROUP, 2024)
The aim of the research is to measure growth performance, absorption capacity and mandatory regional expenditure. The research was carried out at the Jayapura City Government, the object was Regional Expenditures for the 2019-2023 budget period. The research approach is quantitative to discover scientific phenomena of regional shopping. This research produces a scientific phenomenon that the growth and absorption capacity of the total expenditure budget shows an average growth in Regional Expenditures of 5.26%, accompanied by a budget absorption of 97.10%, which has an impact on the impact of Covid-19. The performance measure of meeting the budget (mandatory expenditure) for the 2019-2023 fiscal year period can be assessed as having non-compliant performance.